Examining Script Evolution through Language Contact: The Case of Naxi Manuscripts and Chinese Characters - Dai, Antong; Lin, Ziqing (CV. Tripe Konsultan, 2025)
This study explored the impact of language contact on written languages through the case study of Chinese character borrowing in Naxi Manuscripts. Drawing from four primary corpora spanning religious, medical, and divinatory genres, the study identifies 11 frequently borrowed Chinese characters and 301 instances of borrowing through a combination of optical character recognition (OCR) and manual verification. The borrowing is in three types: phonetic, semantic, and graphic borrowing. Through two proposed indicators,